Effects of different light spectrums on growth and proximate biochemical composition of Chaetoceros calcitrans and marine Chlorella sp. - Tan, Gregory Guan Yuan (2019)
The growth and biochemical composition of microalgae is influenced by light, CO2, nutrients, temperature, pH and mixing. The spectral quality of light source plays an important role in the growth of microalgae and their biochemical composition. Light emitting diodes (LEDs) are an alternative for replacing sunlight and less energy efficient conventional lights as the spectral wavelengths of LEDs can be customized according to species requirements and they consume much less energy. The aim of this study is to examine the growth, proximate biochemical composition and fatty acid profile of Chaetoceros calcitrans and marine Chlorella sp. In the first phase, microlagae were cultivated in small scale photobioreactors (1 L) and exposed to five different spectrums from LEDs – blue, white, green, yellow, red and fluorescent lamp (FL) as the control. In C. calcitrans, yellow light demonstrated the highest (p < 0.05) specific growth rate. Protein content was found to be the highest in the FLcontrol treatment followed by blue and red light, and lowest in yellow light. Lipid content in C. calcitrans was also found to be amongst the highest in yellow along with blue and green light but lowest in white light. Green light treatment had the highest carbohydrate content over the other treatments whereas the lowest was found in white light. The fatty acid content was also found to be influenced by light spectrums. Chaetoceros calcitrans produced highest amounts of ω3 essential fatty acids under red light whereas it was green light for poly-unsaturated fatty acids (PUFAs). Based on the high specific growth rate and lipid production from the first phase, yellow light was selected for the second phase of the experiment which was conducted in flat panel photobioreactors (FP-PBR; 60 L). In phase 2, no significant difference was found in cell density and biomass upon harvest in both yellow and FL-control. However, yellow light demonstrated a higher protein content over FL-control, but showed no significant difference in lipid and carbohydrate. Yellow light also produced the highest PUFAs and ω3 fatty acids. As seen for C. calcitrans, yellow light also demonstrated a higher specific growth rate in marine Chlorella sp. in phase 1. The highest protein content in Chlorella sp. was found in red light while the lowest was in FL-control treatment. However, FL-control showed the highest lipid content. Lowest carbohydrate content was found in red light. In Chlorella sp., red light produced higher amounts of ω3 and PUFAs and green light promoted the synthesis of ω6 fatty acids. Based on the high specific growth rate of Chlorella sp. from the phase 1, yellow light was selected for phase 2 of the experiment which was conducted in flat panel photobioreactors (FP-PBR; 60 L). In phase 2, no significant differences were found in cell density and biomass upon harvesting in both yellow and FL-control. However, yellow light only demonstrated a higher protein content over FL-control, and was significantly lower in lipid and carbohydrate content. Yellow light also produced the highest PUFAs and ω3 fatty acids in Chlorella sp.